2012
DOI: 10.1001/archgenpsychiatry.2011.1870
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotics During Pregnancy

Abstract: Women who used antipsychotics during pregnancy had increased risks of gestational diabetes. The increased risks of giving birth to an SGA infant seemed to be an effect of confounders, such as smoking. Except for macrocephaly, olanzapine and/or clozapine exposure was not associated with anabolic fetal growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(46 citation statements)
references
References 29 publications
(45 reference statements)
2
43
1
Order By: Relevance
“…Thirteen cohort studies, including 6,289 antipsychotic-exposed and 1,618,039 unexposed pregnancies and 6 057 antipsychotic-exposed and 1 641 187 unexposed infants during pregnancy, were eligible for inclusion in this review (Table 1). Three studies were derived from the same population-based cohort(1719) and data from one study were subsequently published as a book(20, 21); therefore, the study reporting the largest population for each outcome was used. All included studies were cohort studies with data derived from birth registries and teratology information services (TIS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen cohort studies, including 6,289 antipsychotic-exposed and 1,618,039 unexposed pregnancies and 6 057 antipsychotic-exposed and 1 641 187 unexposed infants during pregnancy, were eligible for inclusion in this review (Table 1). Three studies were derived from the same population-based cohort(1719) and data from one study were subsequently published as a book(20, 21); therefore, the study reporting the largest population for each outcome was used. All included studies were cohort studies with data derived from birth registries and teratology information services (TIS).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported mean gestational age,(13, 17, 26) which included 730 antipsychotic-exposed and 357 947 unexposed infants. Infants exposed to antipsychotics were born earlier than unexposed infants, but this effect on gestational age was not statistically significant (Figure 4B; WMD = −0.21wks, 95% CI −0.44wks – 0.01wks, p = 0.06).…”
Section: Resultsmentioning
confidence: 99%
“…49 Another study also using Swedish registry data, but from 2005 to 2009 estimated atypical antipsychotic use during pregnancy to be approximately 0.1%. 50 We found that quetiapine, olanzapine and risperidone were the three most commonly prescribed atypical antipsychotics both before and after pregnancy. This mirrors the patterns of atypical antipsychotics dispensed in the USA 37 and the general prescribing pattern of antipsychotics in the UK.…”
Section: Psychotropic Medication Prescribed Before During and After mentioning
confidence: 87%
“…Other research on antipsychotic treatment in pregnancy includes pharmacovigilance studies from drug companies' safety databases 76,77 as well as cohort studies based on various data sources. 38,50,[78][79][80][81][82][83][84][85] A systematic review 19 of many of these studies suggested that women requiring antipsychotic treatment during pregnancy have a higher risk of adverse birth outcomes. However, there was substantial heterogeneity between the studies and Coughlin et al 19 emphasise that most studies had limited adjustment for potential confounding and therefore the observed associations may not be causal.…”
Section: Antipsychoticsmentioning
confidence: 99%
“…As our knowledge of the effects of exposure to the newer antipsychotics during pregnancy is limited, Boden et al [9] investigated the effects of maternal use of antipsychotics during pregnancy on gestational diabetes and fetal growth in a population-based cohort study comparing women exposed and not exposed to antipsychotics during pregnancy. They used the Swedish national health registers for all women giving birth in Sweden between July 1, 2005 and December 31, 2009, with exposure to antipsychotics defined as prescriptions filled.…”
Section: Treatment Of Schizophreniamentioning
confidence: 99%